(untitled) - Hansen, L. Scott (New York, 2013)
This innovative new Autodesk Inventor 2013 book focuses on teaching people mastery of Autodesk Inventor 2013 with a 'Learn by Doing' pedagogical framework.
Keywords: Autodesk Inventor (Electronic resource),Autodesk Inventor (Nguồn điện)